Scheme and experiment of fast frequency hopping communication system based on SDR - Chengyu WEN; Conghui LIAO; Hang XIONG; Hong DU (Tongxin xuebao)
A fast frequency hopping scheme based on SDR was proposed to solve the problem that the existing fast frequency hopping communication system relied on satellite timing.Firstly, a true random sequence was used to perform frequency hopping operation on the modulated signal in this scheme.And the frequency hopping table was obtained by channel down-conversion, low-pass filtering and amplitude peak detection operations.Secondly, the receiver searched for the precise starting point by the peak-to-peak distribution characteristics of the quadrature demodulation amplitude of the baseband signal after de-hopping.Finally, down-conversion was performed and the peak-to-peak amplitude of the quadrature demodulation was checked for exceeding the threshold value to achieve de-hopping for frequency hopping signals.The effectiveness and adaptability of the proposed scheme is verified by using two general-purpose SDR devices with a hopping rate of four hops per symbol period in a real channel with other continuous signals.